The Mobile Apps Development of Simple Machine Content to Improve Learning Achievement of Junior High School Students - Saprudin, Saprudin; Tomia, Amalia; Muhammad, Nurlaela; Rahman, Nurdin Abdul; Hamid, Fatma; Sahjat, Sumarni (Technium Social Sciences Journal, 2023)
This research aims to develop the content for Mobile Apps for simple machine learning materials and to study the validity and the impact of its product on improving junior high school students learning achievement. This development research follows the stages of ADDIE (Analysis, Design, Development, Implementation, Evaluation). The instruments used in this study include Mobile Apps product validation sheets and 30 multiple-choice questions. The validation results of media experts, material experts, and language experts state that this Mobile Apps product is suitable to be used in the learning process. The results of the implementation involving 24 students of class VIII at a junior high school in Ternate city show that the use of Mobile Apps can improve students’ learning achievement